Properties of strong-coupling magneto-bipolaron qubit in quantum dot under magnetic field - 白旭芳 张颖 乌云其木格 额尔敦朝鲁 (Chinese physics B, 2016)
Based on the variational method of Pekar type, we study the energies and the wave-functions of the ground and the first-excited states of magneto-bipolaron, which is strongly coupled to the LO phonon in a parabolic potential quantum dot under an applied magnetic field, thus built up a quantum dot magneto-bipolaron qubit. The results show that the oscillation period of the probability density of the two electrons in the qubit decreases with increasing electron–phonon coupling strength α, resonant frequency of the magnetic field ωc, confinement strength of the quantum dot ω0, and dielectric constant ratio of the medium η; the probability density of the two electrons in the qubit oscillates periodically with increasing time t, angular coordinate φ2, and dielectric constant ratio of the medium η; the probability of electron appearing near the center of the quantum dot is larger, and the probability of electron appearing away from the center of the quantum dot is much smaller.